Enhancing Risk Management Maturity in an Indonesian Government Organization: Strategic Approaches for Enterprise Risk Management Adoption - Simanjuntak, Ria Anggraini; Premananto, Gancar Candra (Coopetition : Jurnal Ilmiah Manajemen, 2026)
This research aims to develop strategic recommendations to enhance the risk management maturity of XYZ, an Indonesian government organization in the process of implementing the Enterprise Risk Management (ERM) approach. A qualitative case study method is employed in this research. Findings from interviews and documentation reveal that XYZ still applies a traditional, non-comprehensive approach to risk management. The Risk Management Index (RMI) analysis identified sixteen key improvement areas, especially for organizations transitioning from traditional to ERM implementation. The proposed strategies include finalizing the ERM policy, integrating risk management performance indicators into the organization's strategic plan, activating the risk management structure, strengthening employees’ risk management competencies, and developing risk management automation.